Agricultural diversification and intra-household dietary diversity: Panel data analysis of farm households in Bangladesh - Alam, Mohammad Jahangir; Begum, Ismat Ara; Mastura, Tamanna; Kishore, Avinash; Woodhill, Jim; Chatterjee, Kuhu; Jackson, Tamara (2023)
This paper investigates the associations between agricultural diversification and dietary diversity among men, women and children of farm households in Bangladesh. Using three waves of nationally representative Bangladesh Integrated Household Survey (BIHS- 2011–12, 2015 and 2018) data and a panel data model, the study found that agricultural production diversification can emphasize the dietary diversification across the life cycle of farm household members. The balanced panel data reveals that agricultural production diversification has a statistically significant and positive impact on dietary diversity of individual members (men, women and children) of farm households. Moreover, other important factors that impact on agricultural diversification and improve dietary diversity like women’s education and employment, commercialization of farm households, access to non-farm income sources, and access to information facilities also have a strong association in improving dietary status, food and nutritional security as well. Although there is currently limited diversity in the diets of adult men, women and children of rural farm households, the situation can be improved over time with proper and consistent support. The findings suggest policy interventions should target not only agricultural diversification but also improve women’s education and on and off farm employment opportunities and facilitate better access to information for rural households. These recommendations can support improved dietary diversity for all household members under different settings.